Rice Productivity and Water Use Efficiency under Different Irrigation Management System in North-Western India (Indian Journal of Extension Education, 2022)
Rice (Oryza sativa L.) is an important kharif cereal crop with huge irrigation water demand. Over the years, several water saving technologies have been developed, tested and disseminated among farming community for enhancing irrigation water productivity in rice. The present study, compared continuous flooding (T1), alternate wetting and drying in which irrigation is done 2 days after seepage (AWD; T2), soil matric potential (ψm;tensiometer guided) based irrigation scheduling at ψm=15kPa (T3) and ψm=20kPa (T4) using PAU tensiometer on basmati rice (var. Pusa Basamti-1121) productivity and water use efficiency (WUE). The results revealed significantly (p<0.05) higher rice grain yield (38.85 t ha-1) under T2, compared with the other irrigation scheduling methods. The AWD (T2) method of irrigation scheduling resulted in saving of 27 per cent irrigation water,compared with T1. The water productivity in basmati rice production was 0.285 kg m-3,0.446 kg m-3, 0.414 kg m-3 and 0.528 kg m-3, respectively in four compared irrigation scheduling methods. As in Punjab around 3.0 Mha area is under rice cultivation and if we adopt irrigation after 2-3 days of seepage it will save around 27 per cent water as compared to continuous flooding amounting about 9.6 billon m3 of water.